ANTESEDEN KEPUASAN PELANGGAN DAN PENGARUHNYA TERHADAP POSITIF WORD OF MOUTH PADA PENGGUNA SMARTPHONE SAMSUNG - Putra, Pramudita Adriant; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
The background of this study is the decreasing index of word of mouth on smartphone Samsung in 2014, it indicates the decline in quality of Samsung, which means that people are no longer talk about Samsung smartphone. The objective of this study is to analyze the effects of product design, product quality assurance, and various feature application on customer satisfaction as an intervening variable and its influence on positive word of mouth of Â the â€œSamsungâ€ smartphone. Â Â  The study distributed 200 questionnaires to Samsung smartphone users. The sampling method employed was a purposive sampling technique. Using SPSS 18.0 and AMOS 18.0, the Structural Equation Modelling (SEM) was run. Â Â Â Â Â Â Â Â Â Â Â  The results showed that the model developed in the study was in good fit as Chi Square = 107 809 with probability = 0.156; RMSEA = 0.027; TLI = 0.989; CFI = 0.991; GFI = 0.939 andÂ  AGFI = 0.912. Partially, product design, product quality and various feature application show positive effects, namely 0.321, 0.234 and 0.268, respectively, on customer satisfaction, while customer satisfaction also indicates a positive effect (0.226) on positive word of mouth. This implies product design is the most important factor of Samsung smartphone influencing customer satisfaction